St. Gregory Palamas on the Divine Simplicity - Plested, Marcus (Modern theology, 2019)
Plested focuses on the doctrine of divine simplicity according to Gregory Palamas (1296-1357/9). He is well aware of the long tradition in the West of considering Palamas's distinction between the divine essence and the energies to do harm to the reality of divine simplicity-even if many recent books on divine simplicity ignore Palamas. Plested thinks that this is in part due to the selectivity of Western readings of Palamas's corpus. Although for Palamas the divine essence is truly (not merely conceptually) distinct from what Plested terms the divine "actualizations," Palamas insists repeatedly that his point does not undermine absolute divine simplicity. In fact, as Plested shows, Palamas considers that the real distinction between essence and energies not only supports, but indeed flows from, the doctrine of divine simplicity properly understood. Plested admits that recent Orthodox interpreters of Palamas, such as John Meyendorff and Vladimir Lossky, tend to give little attention to divine simplicity except by way of contrast with Western accounts of the doctrine. But Plested argues that Palamas's doctrine of divine simplicity is better interpreted as in accord with the fundamental intuitions of his Latin contemporaries, even if expressed in a different metaphysical framework. Examining certain lesser-known works of Palamas, Plested identifies a set of important interpretative keys for understanding Palamas's account of divine simplicity, including the normative role of the principles of the Sixth Ecumenical Council (680-1) and the necessity of appreciating the historical contexts in which he wrote specific works.